A Socio-Cultural Perspective of Women Education and Empowerment in Rural Bangladesh - Sultana, Mst (2006)
The main focus of this study was to examine the role of education in increasing the level of women's empowerment particularly in the decision-making process at the household level and to find out how the socio-cultural factors (for genderbased awareness and the use of Purdah-related norms) influence women's education as well as empowerment in rural Bangladesh. The study was conducted in one of the districts of Dinajpur in Bangladesh. Three villages namely, Mashimpur, Mohiskotha and Jugibari which are situated under the Union of Auliapur at Sadar thana (sub-district) were chosen as study areas. The respondents of the study consisted of 340 women from the selected areas. To gather qualitative information, 27 respondents were also involved in this study. In order to gather the depth information, both quantitative and qualitative methods were employed in this study. The first objective of the study was to examine the awareness of gender-based factors in rural women's education as well as their empowerment. The study showed that in Bangladesh, socio-cultural ideology generates gender-based inequalities in education. As a result of the patriarchal ideology, most respondents consider sons as 'assets'. On the other hand, daughters are treated as nonpermanent family members in their natal home since they will move into their husband's house after marriage. Due to such beliefs and practices, women received less attention in education and as a result lack empowerment. The second objective of the study was to identi@ the role of the practice of Purdah-related norms and its influence on rural women's education as well as their empowerment. The results indicated that in Bangladesh most respondents had a 'non-traditional' ideology or non-conservative ideology about the practice of Purdah. Correlation coefficient was also conducted to examine the relationship between respondent's Purdah ideology and the socio-economic variables and the results showed that among the socio-economic variables religious status, education, occupation, income, total number of children and son's education were positively correlated with Purdah awareness although the strength of the relationship was weak. The third objective of the study was to examine the role of education and how education might help in increasing women's decision-making power (empowerment) at the household level. The results showed that women with higher education level i.e. those with higher secondary education and graduates, had more decision-making power compared to illiterate, primary and secondary educated women. Similarly, it was found that the women who full-time employed had more decision-making power than housewives and self-employed women. The findings also showed that respondent's educational attainment (r 4.47; p<0.01), occupation (r = 0.61; p<0.01) and income (r = 0.60; p<0.01) were positively related to their decision-making power. The fourth objective of the study was to determine the factors (particularly the independent variables) that might affect women's decision-making power (empowerment) at the household level. A multiple linear regression analysis was carried out and the results revealed that education, occupation, income and genderbased awareness had a significant influence on women's decision-making power (the level of empowerment). The analysis of variance (ANOVA) showed the overall significant of the linear regression model with F-test (p<0.001) for considerable adjustment of the model with the regression coefficient (R square) of 5 1.6. Overall, the study suggests that improvement in women's access to education particularly the higher level of education opportunities would increase women's employment and income. This could expand their ability to make decisions in the family and would play a key role in the empowerment of rural women.